Changes in the expression of miR-103a and miR-21: a functional diagnosis of toxocariasis in rats. Issue 5 (26th May 2022) - Zibaei, Mohammad; Rokni, Mohammad Bagher; Sohrabi, Nasrin; Sepahvand, Asghar; Raiesi, Omid; Getso, Muhammad Ibrahim; Alizadeh, Gita; Ibrahim, Asmaa; Yarahmadi, Mohammad; Raissi, Vahid
Abstract : Introduction. Toxocariasis is a zoonotic parasitic disease caused by migrating nematode worms, Toxocara species larvae, within tissues. MicroRNAs (miRNAs) are small RNA molecules that regulate gene expression at a post-transcriptional level. Hypothesis/Gap Statement. miRNA-based diagnostic biomarkers for toxocariasis are emerging, but there is limited information about the role of many miRNAs and a more detailed diagnostic evaluation of miRNA expression patterns is needed to understand their immunobiological function. Aim. We investigated the expression levels of circulating miRNA 21 and miRNA 103a as potential biomarkers for the prediction and diagnosis of toxocariasis in Wistar rats infected with Toxocara canis . Methodology. Thirty Wistar rats were inoculated orally with 2500 T. canis embryonated eggs via gavage. Serum samples were collected from infected animals and were tested against T. canis antigens for 60 days post-infection. The plasma samples were isolated for quantitative real-time PCR (qPCR) assays and qPCR was used to assess transcription levels of miRNA 21 and miRNA 103a. Results. The prevalence of anti- Toxocara IgG was detected in 7/30 (23.3 %) infected rats. Molecular analysis of miRNAs 21 and 103a  showed that expression levels of miRNAs in both groups of Toxocara -positive and negative samples were the same without significant association. The ratio of housekeeping gene expression ( U6 ) to gene expression of miRNAs 21 and 103a indicated the rate of change (1/1.38 ≈ 0.75 and 1/0.751 ≈ 1.3, respectively). Conclusion. Our study revealed that miRNAs 21 and 103a  might play fundamental roles as biomarkers and diagnostic tools for toxocariasis. However, the changes in expression of these miRNAs were not adequate to be used as biomarkers in diagnosis.